Challenges in the management of pediatric ruptured brain arteriovenous malformation: a case report - Celia, Celia; Susilawati, Susilawati; Cahyo, Johanes Ari; Shen, Robert; Fenia, Irene (Paediatrica Indonesiana, 2024)
Brain arteriovenous malformations (bAVMs) are intracranial vascular lesions characterized by abnormal connections between the arterial and venous systems without an interposed capillary bed. Pediatric bAVMs constitute merely 12–18% of all diagnosed bAVMs, but an initial finding of bAVM rupture occurs more frequently in the pediatric population than in adults, accounting for 58–77% of all pediatric bAVM admissions.1,2 Although spontaneous pediatric intracerebral hemorrhage has an annual incidence of 1.4 per 100,000 people per year, it carries a risk of severe permanent neurological deficits, occurring in 20–40% of patients and significant mortality in up to 25% of affected individuals.3,4,5 Ruptured bAVMs are the cause of 30-50% of intracranial hemorrhages in the pediatric population and the most common cause of hemorrhagic stroke in children.1 Current therapeutic approaches for ruptured bAVMs in children include open microsurgery, endovascular embolization, as well as stereotactic radiosurgery (SRS), be it isolated or as a multimodal treatment strategy. Herein, we present the case of a 6-year-old boy with a ruptured bAVM successively managed with hemicraniectomy decompression and intracranial bleeding evacuation, followed by stereotactic radiosurgery (SRS) using gamma knife for the small AVM which was inaccessible during open surgery.